Prevalence and management of oropharyngeal dysphagia in patients with severe anorexia nervosa: A large retrospective review. Issue 2 (28th August 2015) - Holmes, Samantha R.M.; Sabel, Allison L.; Gaudiani, Jennifer L.; Gudridge, Tricia; Brinton, John T.; Mehler, Philip S.
ABSTRACT: Objective: Oropharyngeal dysphagia (OPD) refers to difficulty swallowing food or a liquid bolus from the oral and pharyngeal cavities into the esophagus and increases the risk of possibly life‐threatening pneumonia. Little has been reported on OPD in adults with anorexia nervosa (AN). This study includes a description of OPD in severe AN and discusses potentially effective clinical management. Method: Two hundred and six adults with severe AN, admitted over a five‐year period to a national referral center specializing in the multidisciplinary medical stabilization of this population, were retrospectively evaluated by electronic database query and manual chart review. All patients whose initial medical assessment triggered a speech‐language pathology (SLP) consultation, due to concerns for OPD, were reviewed in detail. Results: Of the 206 total patients, 42 presented with symptoms of OPD and received SLP consultation. In the OPD cohort, 37 (88%) were women, with median age 32 years old, and mean admission weights of 57% ideal body weight (IBW) and body mass index (BMI) of 12 kg/m 2 . Compared with those who did not have OPD, OPD patients had significantly lower BMI on admission (12 kg/m 2 vs. 13.1 kg/m 2, p  < 0.001), longer stay (21 days vs. 14 days, p  < 0.001), and were more medically compromised, including a greater incidence of refeeding hypophosphatemia (60.9% vs. 29.7%, p  < 0.004). Discussion: Clinical awareness of OPD may reduce the incidence of aspiration pneumonia and promote life‐saving oral nutrition in patients with severe AN. Proper, timely evaluation and intervention may improve clinical outcomes. © 2015 Wiley Periodicals, Inc. (Int J Eat Disord 2016; 49:161–168).